The Statute and the Judge - Peretiatkowicz, Antoni (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2019)
The paper is an English translation of Prąd nowy w prawoznawstwie. Ustawa a sędzia by Antoni Peretiatkowicz, published originally in Pol-ish in 1916. The text is published as a part of a jubilee edition of the “Adam Mickiewicz University Law Review. 100th Anniversary of the Faculty of Law and Administration” devoted to the achievements of the late Professors of the Faculty of Law and Administration of the Adam Mickiewicz University, Poznań.